HYPOTHETICAL LEARNING TRAJECTORY DESIGN IN REFLECTION LEARNING USING THE CONTEXT OF THE CIREBON RED MOSQUE - Hamidah, Ida; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Ely; Nusantara, Duano Sapta (Jurnal Pendidikan Matematika (JUPITEK), 2024)
This research aims to design a reflective learning trajectory using the context of the Cirebon Red Mosque as the starting point or learning context. The method used in this research is design research with stages of preliminary design, design experiment and retrospective analysis. The subjects in this research were several samples of class VIII junior high school students. The results of this research are a hypothetical learning trajectory design in reflective learning using the context of the Cirebon Red Mosque with a learning trajectory, namely students observing pictures from the front gate of the Red Mosque, having discussions and finding the meaning and properties of reflection, students drawing objects with agreed conditions, students record the starting point and ending point of the reflection results and find the relationship between the two and finally, students find the reflection formula. The research results show that a series of activities in the context of the Cirebon Red Mosque have a potential impact on understanding the concept of reflection. Students work on mathematics collaboratively and the learning process becomes meaningful and easy.